1988
DOI: 10.1152/jappl.1988.65.4.1539
|View full text |Cite
|
Sign up to set email alerts
|

Reflex effect of skeletal muscle mechanoreceptor stimulation on the cardiovascular system

Abstract: To determine the potential for mechanical stimulation of skeletal muscle to contribute to the reflex cardiovascular response to static contraction (exercise reflex), we examined the cardiovascular effects caused by either passive stretch or external pressure applied to the triceps surae muscles. First, the triceps surae were stretched to an average developed tension of 4.8 +/- 0.3 kg. This resulted in increases in mean arterial pressure (MAP) of 28 +/- 7 mmHg, dP/dt of 1,060 +/- 676 mmHg/s, and heart rate (HR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
146
6
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(163 citation statements)
references
References 0 publications
10
146
6
1
Order By: Relevance
“…Indeed, passive stretch of the hindlimb triceps surae muscle increased HR by 6 -11 beats/min and MAP by 14 -46 mmHg in anesthetized (27)(28)(29)39) or decerebrate cats (33); passive stretch of the forelimb triceps brachii muscle increased HR by 16 beats/min and MAP by 38 mmHg in anesthetized cats (17). Moreover, passive stretch increased cardiac sympathetic efferent nerve activity by ϳ40 -50% (29,33) and renal sympathetic efferent nerve activity by ϳ20% (27,28) in anesthetized or decerebrate cats and decreased cardiac vagal efferent nerve activity by ϳ30% (33).…”
Section: Stimulation Of Mechanosensitive Afferents Causes Increases Imentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, passive stretch of the hindlimb triceps surae muscle increased HR by 6 -11 beats/min and MAP by 14 -46 mmHg in anesthetized (27)(28)(29)39) or decerebrate cats (33); passive stretch of the forelimb triceps brachii muscle increased HR by 16 beats/min and MAP by 38 mmHg in anesthetized cats (17). Moreover, passive stretch increased cardiac sympathetic efferent nerve activity by ϳ40 -50% (29,33) and renal sympathetic efferent nerve activity by ϳ20% (27,28) in anesthetized or decerebrate cats and decreased cardiac vagal efferent nerve activity by ϳ30% (33).…”
Section: Stimulation Of Mechanosensitive Afferents Causes Increases Imentioning
confidence: 95%
“…We have reported that cardiac and renal sympathetic efferent nerve activities abruptly increase immediately before or at the onset of voluntary muscle excursion, suggesting that central command has a predominant role in regulating the cardiovascular system during exercise (23)(24)(25). On the other hand, passive mechanical stretch of skeletal muscle, which is assumed to predominantly stimulate mechanoreceptors, increases HR, AP, and respiration in anesthetized animals and humans (8,39). Furthermore, passive stretch increases cardiac and renal sympathetic nerve activities (27)(28)(29) but decreases cardiac parasympathetic nerve activity (33).…”
mentioning
confidence: 99%
“…For example, external compressions applied to skeletal muscle produce a small increase in blood pressure in animal models. 25 In humans, thigh occlusion to suprasystolic pressure contributes to the elevated mean arterial pressure presumably through the stimulation of mechanoreceptor afferents. 26 In addition to cuff inflation itself, different cuff position 27 and the duration of occlusion 28 can induce different hyperaemic response.…”
Section: Discussionmentioning
confidence: 99%
“…This is because passive muscle stretch is a maneuver to selectively excite mechanically sensitive muscle afferents, thereby allowing us to focus on roles for the muscle mechanoreflex. It was demonstrated in anesthetized cats that the blood pressure was reflexly elevated by passively stretching the triceps surae muscles, which did not generate any muscle metabolites 42) . Subsequent electrophysiological studies demonstrated stimulation of mechanically sensitive group III muscle afferents 43) , cardiac 39) and renal 40) SNA increases, as well as vagal withdrawal 44) , in response to muscle stretch in anesthetized or decerebrate cats.…”
Section: Exercise Pressor Reflex Arcmentioning
confidence: 99%